2023
DOI: 10.31219/osf.io/h2fv5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-National Variations in Adolescent Sleep Patterns: A Time-Use Study

Joan Garcia-Roman,
Pablo Gracia,
Giulia Zerbini

Abstract: INTRODUCTION: Adolescents’ poor sleep is a major public health problem that can be influenced by national context. This study adopts a novel 24-hour approach to examine cross-country variations in adolescents’ sleep patterns.METHODS: We use high-quality 24-hour time-diary data from the Multinational Time Use Study (N = 25,248 diaries; mean age 15.4 years; 50.3% girls) across nine countries (i.e., Finland, France, Hungary, Italy, Netherlands, South Africa, South Korea, Spain, and the UK) to examine cross-countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Empirical studies have found that insufficient sleep, which is typically measured as less than eight hours per day of sleep among teenagers, is associated with adolescent increased mental health, physical health problems and poorer school performance (Chaput et al, 2016;Henderson et al, 2019;Master et al, 2023;Quach et al, 2016). While examining the quantity of child and adolescent sleep does not give a perfect estimate of the actual quality and experience of their sleep, scientists can provide evidence on key markers of young people's present and future well-being by analysing high-quality time-diary data on the frequency and timing of sleep (Garcia-Roman et al, 2023).…”
Section: Sleep Timementioning
confidence: 99%
“…Empirical studies have found that insufficient sleep, which is typically measured as less than eight hours per day of sleep among teenagers, is associated with adolescent increased mental health, physical health problems and poorer school performance (Chaput et al, 2016;Henderson et al, 2019;Master et al, 2023;Quach et al, 2016). While examining the quantity of child and adolescent sleep does not give a perfect estimate of the actual quality and experience of their sleep, scientists can provide evidence on key markers of young people's present and future well-being by analysing high-quality time-diary data on the frequency and timing of sleep (Garcia-Roman et al, 2023).…”
Section: Sleep Timementioning
confidence: 99%